Analysis of policy towards improvement of perinatal mortality in the Netherlands (2004–2011). (May 2016) - Vos, Amber A.; van Voorst, Sabine F.; Steegers, Eric A.P.; Denktaş, Semiha
Abstract: Relatively high perinatal mortality and morbidity rates 2 in the Netherlands resulted in a process which induced policy changes regarding the Dutch perinatal healthcare system. Aims of this policy analysis are (1) to identify actors, context and process factors that promoted or impeded agenda setting and formulation of policy regarding perinatal health care reform and (2) to present an overview of the renewed perinatal health policy. The policy triangle framework for policy analysis by Walt and Gilson was applied 3 . Contents of policy, actors, context factors and process factors were identified by triangulation of data from three sources: a document analysis, stakeholder analysis and semi-structured interviews with key stakeholders. Analysis enabled us to chronologically reconstruct the policy process in response to the perinatal mortality rates. The quantification of the perinatal mortality problem, the openness of the debate and the nature of the topic were important process factors. Main theme of policy was that change was required in the entire spectrum of perinatal healthcare. This ranged from care in the preconception phase through to the puerperium. Furthermore emphasis was placed on the importance of preventive measures and socio-environmental determinants of health. This required involvement of the preventive setting, including municipalities. The Dutch tiered perinatal healthcare system and divergent views amongst curative perinatal health care providers were important context factors. This study provides lessons which are applicable to health care professionals and policy makers in perinatal care or other multidisciplinary fields. Highlights: Perinatal mortality rates triggered a policy process to change perinatal care. Parliamentary questions and interest from the media triggered policy renewal. Public health policy makers were engaged in perinatal policy reform. Newly formed policy included social environmental factors in perinatal health. A role was defined for municipal involvement in perinatal healthcare.